Avrupa Birliği uyum sürecinde Türk sigorta sektörünün gelişimi - Aydınalp, Nuray (My University, 2012)
gorta Sektörü, Avrupa Birliği Sigorta Sektörü ÖZET Günümüzde meydana gelen entegresyon hareketleri tüm dünyada yapılmakta olan üretim, sunulmakta olan hizmetlerin belirli standartlara ulaştırılması ve şirketlerin ayakta durabilmesi için oldukça önem taşımaktadır. Bu bakımdan Türkiye’nin Avrupa Birliği’ne üyelik müzakere sürecinde Avrupa Birliği standartlarına uyması gerekmektedir. Avrupa Birliği uyum sürecinde bazı düzenlemeler yapılmıştır. Bu düzenlemeler başta Bankacılık sektörü olmak üzere sigortacılık sektöründe meydana gelmiştir. Çalışmada Avrupa Birliği’ne tam üyelik için müzakere aşamasında olan ülkemizin Türk sigorta sektörü incelenmiş ve Avrupa Birliği üyesi ülkelerin sigorta sektörünün verileri ile kıyaslanması yapılmıştır. TURKISH INSURANCE SECTOR IN THE PROCESS OF DEVELOPMENT OF COMPLIANCE WITH THE EUROPEAN UNION Insurance Sector in Turkey, Insurance Sector in the European Union .

Today entegresyon movements that occur all over the world who made the production, delivery, and companies with specific standards of services that are offered are very important prosthetic limb. In this regard, Turkey's EU membership negotiation process required to comply with European Union standards. Some changes were made to the European Union harmonization process. These arrangements have occurred in the insurance sector, particularly in the banking sector. The study of the negotiation stage of our country for full membership in the European Union, the Turkish insurance sector were analyzed and comparisons were made with data from European Union member countries, the insurance industry.
Keywords: Avrupa Birliği_Sigortacılık; Sigortacılık; Sigortacılık_Türkiye